ЕСТЕТИЧНЕ ВИХОВАННЯ УЧНІВ СЕРЕДНІХ КЛАСІВ ЗАСОБАМИ ВИРАЗНОГО ЧИТАННЯ (Педагогіка вищої та середньої школи, 2004)
Different problems and aspects of bringing up of spirit among young generation in studiing Ukrainian literature are opened in this article.